Design and Finite Element Analysis of Lawn Mower Machine - Rozi Saferi; Asmara Yanto; Joko Sucipto (Jurnal Teknik Mesin (JTM), 2020)
Technological advances are now being found in everyday, one of them is an android smartphone. Android can be used to control motor speed without using cables with the help of microcontroller, motor driver and bluetooth module. In this study the autors designed and performed static analysis on the framework an android-based lawn mower using Autodesk Inventor. This grass cutting machine consists of several components, that is: framework, battery, microcontroller, motor driver, relay 5v, bluetooth module and others. The design result of an android-based lawn mower have a whole dimension with length = 298.89mm, width = 334.88mm and high = 241.02mm.  After static analysis is carried out on the framework obtained results: Displacement minimum 0 mm and displacement maximum 0.0909735 mm, Safety factor minimum 1.93351 and safety factor maximum 15.